Well sealing technologies with the possibility of controlling the rheological properties of cement composite by external influence - Klimov Dmitry (EPJ Web of Conferences)
The problem of long-term tightness of oil and gas wells is extremely acute for the oil and gas industry, both in terms of efficient and trouble-free operation of wells, and the most serious environmental problems associated with leaks and gushers of oil and gas at operating and abandoned wells. The article presents an up-to-date review of experimental studies, promising traditional and alternative technologies for completing and abandoning wells in difficult thermobaric operating conditions or associated with temperature and other influences to activate and control the rheological properties of cement compositions. When cementing wells in difficult geological conditions, the oil and gas industry faces the problems of creating plugs capable of withstanding extremely high pressures, temperatures and loads. In this case it makes sense to consider plugging technologies based on self-healing and regeneration effects, thermite compositions, eutectic metals, thermosetting resins and polymers. Based on the analysis of modern cementing materials and well sealants, the author proposes a set of key characteristics that a cement slurry should have in order to be able to control its physical and mechanical properties and its ability to re-liquefy under the influence of temperature, pressure or other external factors.